Development and Improvement of the Hydraulic Coconut Dehusking Machine - - (Agriculture and Natural Resources, 1992)
Two sets of the hydraulic coconut dehusking machine were developed. Their hydraulic and electrical control circuits were connected in series to enable them operating contemporaneously. Each machine consists of the frame, a lifting mechanism, a dehusking mechanism, an ejecting mechanism, and a nuts’ pan. During operation, each operator put a coconut on the lifting mechanism in order to start the working cycle automatically. As a result, the nuts are immediately pushed up and seized by the holding teeth under the supplement of the hydraulic reducing circuit. After that the dehusking mechanisms started operations via the sequence circuit. At the end of the cycle, both mechanisms returned to their original positions. Some remaining fibrous was taken out manually after the next cycle is started. The continuous dehusking speed was found to be 22.2 seconds per 2 coconuts.